INTRODUCING ENGLISH VOCABULARY TO YOUNG EFL LEARNERS AT ELEMENTARY SCHOOL LEVEL BY USING FLASHCARDS - Ni Made Likhita Ananda; Ni Luh Christine Prawitha Sari Suyasa; Putu Chris Susanto; Putu Chrisma Dewi; I Gede Neil Prajamukti Wardhana (LPPM Universitas Dhyana Pura, 2023)
This project aimed to introduce English vocabulary to young EFL learners at theelementary school level by using flashcards as a visual and interactive tool in order toincrease the effectiveness and engagement of vocabulary learning among young learners.It was carried out at BPI Fajar Kasih Siulan, with four boys and six girls in grades 1 to 3of elementary school participating. The project consisted of three phases, namelyobservation, teaching phase using flashcards, and evaluation. The use of flashcards isexpected to improve vocabulary acquisition among young learners by increasing theirunderstanding, memory, and motivation to learn English. The evaluation stage showedpositive results in the form of improved ability to recognize and recall vocabulary, and lessreliance on dictionaries—indicated by 97% recall at the end of the project for allvocabularies introduced, compared to only 45% initially. This project has potentialimplications for parents, schools, teachers, education authorities and young learners. Itmay pave the way for future development by exploring the use of technology andgamification to further enhance English language learning.